Imaging Features of Urachal Cancer: A Case Report - Chen, Xiaoyan; Kang, Chunsong; Zhang, Mingxia (Frontiers in Oncology, 2019)
Urachal Cancer originates from the space of Retzius. It is a rare but aggressive carcinoma. Typical images of urachal cancer are rare, and this report provides a characteristic ultrasonographic imaging of this case. Herein, we present a case of a 45-year-old male patient with painless hematuria of 1-week duration with no obvious cause. Analysis of the characteristics of ultrasound images in this case is as follows: 1. a solid mass located between the top of the bladder and the abdominal wall, with an irregular shape, unclear boundary, and invading the bladder wall; 2. low tumor echogenicity, unevenly distributed, with a small amount of calcification; and 3. patchy and short-line blood flow signals within the mass. Postoperative pathology confirmed urachal adenocarcinomas.